2012
DOI: 10.1063/1.4768684
|View full text |Cite
|
Sign up to set email alerts
|

355, 532, and 1064 nm picosecond laser interaction with grass tissues

Abstract: In this article, we investigate how 355, 532, and 1064 nm picosecond lasers interact with grass tissues. We have identified five interaction regimes, and based on this classification, interaction maps have been constructed from a systematic experiment. The optical properties of light absorbing grass constituents are studied theoretically in order to understand how and how much light is absorbed by grass tissues. Scanning electron microscopy and optical microscopy are employed for observing morphological and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In Part I of this study, 8 we found that for k ¼ 355 and 532 nm, laser interacts predominantly with chlorophylls and for k ¼ 1064 nm dry matter is the primary light absorbing constituent of grass. Therefore, at these wavelengths, light is absorbed primarily by grass tissues.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…In Part I of this study, 8 we found that for k ¼ 355 and 532 nm, laser interacts predominantly with chlorophylls and for k ¼ 1064 nm dry matter is the primary light absorbing constituent of grass. Therefore, at these wavelengths, light is absorbed primarily by grass tissues.…”
Section: Introductionmentioning
confidence: 98%
“…The concentrations of water, chlorophylls, carotenoids, and dry matter for Kentucky bluegrass are adopted from Ref. 8 and summarized in Table I. Figure 2 presents the a  C curves for chlorophylls, carotenoids, dry matter, and water from k ¼ 300 nm to 14 lm.…”
Section: Theoretical Investigation Of Grass Optical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations